Penerapan Metode SDLC Waterfall Pada Sistem Pemesanan Makanan Menggunakan QR-Code Berbasis Website - Yolla Putri Ervanisari; Muhamad Koyimatu; Kristine Angelina Simanjuntak; Intan Oktafiani (Prosiding SISFOTEK, 2024)
Café Sudut Temu by Toastea, located in Cirahayu Tegalega Street, Central Bogor, was established in 2015. The manual booking system in place at Café Sudut Temu is currently inefficient and vulnerable to error, resulting in lengthy waiting times, order errors, and challenges in inventory management. Therefore, this research is planning to build a QR code-based food ordering system through a website. The ordering system in this study was developed using the Waterfall methodology and the application was designed using the Laravel PHP framework. The design phase begins with the collection of requirements, the creation of design, the implementation or development of the system and ends with testing. This research results in a system that simplifies the ordering process, reduces errors, and improves operational efficiency.In addition, the responsive design with a mobile-friendly interface allows customers to order directly without having to wait for the help of the server. The system is expected to increase customer satisfaction and contribute to coffee growth amid increasing competition in the industry. The results of this research are a website-based application for ordering food and beverages using a QR Code on Café Sudut Temu.